Clinical significance of T-bet, GATA-3, and Bcl-6 transcription factor expression in bladder carcinoma. Issue 1 (December 2016) - Bahria-Sediki, Islem; Yousfi, Nadhir; Paul, Catherine; Chebil, Mohamed; Cherif, Mohamed; Zermani, Rachida; El Gaaied, Amel; Bettaieb, Ali
Abstract Background The aim of this study was to investigate the clinical significance of three immune cell-related transcription factors, T-bet, GATA-3 and Bcl-6 in bladder cancer in Tunisian patients. Methods Expression of T-bet, GATA-3 and Bcl-6 genes was assessed using RT-qPCR in 65 bladder cancers from patients: 32 being diagnosed as low- and medium-grade, 31 as high-grade, 25 as muscle invasive stage and 39 as non-muscle invasive stage. Gene expression was statistically correlated according to the grade, the stage, tobacco consumption, the BCG response and disease severity. Results T-bet levels in patients with high-grade bladder cancer were significantly elevated compared to patients with low- or medium-grade bladder cancer (p = 0.005). In invasive carcinoma (T2–T4), the T-bet levels were significantly higher than in superficial non-invasive bladder tumors (Tis, Ta, and T1) (p = 0.02). However, T-bet is predictive of the response to BCG. Its expression is high in good responders to BCG (p = 0.02). In contrast, the expression of GATA-3 and Bcl-6 in non-invasive carcinoma (p = 0.008 and p = 0.0003) and in patients with low- and medium-grade cancers (p = 0.001 and p < 0.0001) is significantly higher than in invasive bladder tumors and in patients with high-grade bladder carcinoma, respectively. In addition, heavy smokers, whose tumors express low levels of GATA-3 and Bcl-6, are poor responders to BCG (p = 0.01 and p = 0.03). Finally, better patient survival correlated with GATA-3 (p = 0.04) and Bcl-6 (p = 0.04) but not T-bet expression. Conclusions Our results suggest that T-bet expression in bladder tumors could be a positive prognostic indicator of BCG therapy, even if high levels are found in high-grade and stage of the disease. However, GATA-3 and Bcl-6 expression could be considered as predictive factors for good patient survival.